The role of radiation therapy in patients with primary and metastatic liver tumours - Gliński, Bogdan; Mucha-Małecka, Anna; Jakubowicz, Jerzy; Frączek-Błachut, Beata (Contemporary Oncology/Współczesna Onkologia, 2008)
Technical advances in tumour imaging, radiation therapy planning and patient’s motion management have made possible the evolving role of conformal radiotherapy (CRT) and stereotactic irradiation (STIR) in the treatment of patients with primary and metastatic liver tumours. A variety of doses and fractionation systems have been used in CRT/STIR in combination with other therapies, mainly with transarterial hepatic embolization (TAHE). Outcomes following CRT/STIR alone or CRT/STIR with TAHE appear better than outcomes following similar historical controls or TAHE alone; however, randomized trials are needed to confirm this observation. Excellent local tumour control rates and a promising survival rate with low toxicity are seen using CRT/STIR. The best results are obtained in patients who can be treated with high level doses. In conclusion, radiation therapy of patients with primary and metastatic liver tumours is well tolerated and gives the good results compared to other treatment schedules.